MENGHIDUPKAN ILMU AGAMA DI LEMBAGA PENDIDIKAN TINGGI - Priyono, Sugeng (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
This study aims to explore strategic approaches in learning Islamic religious education in higher education to improve the integration of knowledge, charity, and ikhlas in the lives of students. Using a descriptive qualitative method, this study analyzes the implementation of practice-based learning in Trilogi University, including audiences to MUI, halal product assistance training, and seminars related to national values and technology. The findings show that practice-focused learning methods are able to build students' spiritual awareness, strengthen national values, and improve understanding of the concept of maqashid sharia in daily life. A visit to MUI enriched students' insights into the role of ulama in maintaining community harmony, while halal training emphasized the importance of the halal industry in a global context. The religion and technology seminar provided a critical perspective on the integration of Pancasila values in the development of modern technology. In conclusion, a holistic approach in learning Islamic religious education not only improves theoretical understanding, but also prepares students to become individuals with character, competitiveness, and social responsibility.